2023
DOI: 10.1111/tpj.16529
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate alleviates ammonium toxicity in Brassica napus by coordinating rhizosphere and cell pH and ammonium assimilation

Shuang Li,
Lei Yan,
Wen Zhang
et al.

Abstract: SUMMARYIn natural and agricultural situations, ammonium () is a preferred nitrogen (N) source for plants, but excessive amounts can be hazardous to them, known as toxicity. Nitrate () has long been recognized to reduce toxicity. However, little is known about Brassica napus, a major oil crop that is sensitive to high . Here, we found that can mitigate toxicity by balancing rhizosphere and intracellular pH and accelerating ammonium assimilation in B. napus. increased the uptake of and under high circums… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…Importantly, previous studies have shown that a combined supply of nitrate and ammonium boosts plant growth beyond that observed with the N source provided alone (George et al, 2008;Poothong et al, 2016). Recent reports indicate that NO 3 À can mitigate NH 4 + toxicity by accelerating ammonium assimilation, even at a very low concentration (0.1 mM) (Li et al, 2023;. Similarly, we found that the growth rate of KSR was accelerated when the concentration ratio of ammonium and nitrate was 2: 1 or 1: 2 (Figures 1-2; S3-S5).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Importantly, previous studies have shown that a combined supply of nitrate and ammonium boosts plant growth beyond that observed with the N source provided alone (George et al, 2008;Poothong et al, 2016). Recent reports indicate that NO 3 À can mitigate NH 4 + toxicity by accelerating ammonium assimilation, even at a very low concentration (0.1 mM) (Li et al, 2023;. Similarly, we found that the growth rate of KSR was accelerated when the concentration ratio of ammonium and nitrate was 2: 1 or 1: 2 (Figures 1-2; S3-S5).…”
Section: Discussionsupporting
confidence: 82%
“…Nitrogen (N) is a key macronutrient and has a strong influence on plant growth (Li et al, 2023). Modulating the N levels can lead to changes in morphological, physiological, and biochemical aspects (Wu et al, 2022;Amin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%